2020
DOI: 10.1371/journal.pone.0237440
|View full text |Cite
|
Sign up to set email alerts
|

Temporal patterns in electrical nerve stimulation: Burst gap code shapes tactile frequency perception

Abstract: We have previously described a novel temporal encoding mechanism in the somatosensory system, where mechanical pulses grouped into periodic bursts create a perceived tactile frequency based on the duration of the silent gap between bursts, rather than the mean rate or the periodicity. This coding strategy may offer new opportunities for transmitting information to the brain using various sensory neural prostheses and haptic interfaces. However, it was not known whether the same coding mechanisms apply when usi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 60 publications
(87 reference statements)
1
12
0
Order By: Relevance
“…The mean equivalent tactile perceived frequency for stimulus DA25 was 27.0 Hz (95% CI: 25.3-28.8), for stimulus DA50 was 47.9 Hz (45.0-50.8) and stimulus DA100 was 90.9 Hz (81.9-99.8). Although these values are close to their burst-gap model predicted values depicted by the dashed lines [which correspond to the reciprocal of the inter-burst interval in the test train (Birznieks and Vickery, 2017;Ng et al, 2020Ng et al, , 2021], the data for DA25 and DA100 differed from the predicted values of 25 Hz (p = 0.029, n = 12, one-sample t-test) and 100 Hz (p = 0.047, n = 12, onesample t-test); while for stimulus DA50, there was no statistical difference from the burst-gap predicted value (50 Hz, p = 0.13, n = 12). However, the data for DA25 and DA100 was much more poorly predicted by their periodicity (23 Hz, p = 0.0004; and 67 Hz, p = 0.0001; one-sample t-test) or mean pulse rate (46 Hz, p < 0.0001; and 134 Hz, p < 0.0001) than from burstgap predictions, suggesting the burst-gap model offers a better explanation.…”
Section: Perceptual Equivalence Between Cross-modal Bursting and Regu...supporting
confidence: 65%
See 2 more Smart Citations
“…The mean equivalent tactile perceived frequency for stimulus DA25 was 27.0 Hz (95% CI: 25.3-28.8), for stimulus DA50 was 47.9 Hz (45.0-50.8) and stimulus DA100 was 90.9 Hz (81.9-99.8). Although these values are close to their burst-gap model predicted values depicted by the dashed lines [which correspond to the reciprocal of the inter-burst interval in the test train (Birznieks and Vickery, 2017;Ng et al, 2020Ng et al, , 2021], the data for DA25 and DA100 differed from the predicted values of 25 Hz (p = 0.029, n = 12, one-sample t-test) and 100 Hz (p = 0.047, n = 12, onesample t-test); while for stimulus DA50, there was no statistical difference from the burst-gap predicted value (50 Hz, p = 0.13, n = 12). However, the data for DA25 and DA100 was much more poorly predicted by their periodicity (23 Hz, p = 0.0004; and 67 Hz, p = 0.0001; one-sample t-test) or mean pulse rate (46 Hz, p < 0.0001; and 134 Hz, p < 0.0001) than from burstgap predictions, suggesting the burst-gap model offers a better explanation.…”
Section: Perceptual Equivalence Between Cross-modal Bursting and Regu...supporting
confidence: 65%
“…The inter-burst intervals in test trains were set at 40, 20, and 10 ms to correspond to expected perceived frequencies of 25, 50, and 100 Hz, respectively, for the doublet acoustic (DA25, DA50, and DA100) (Sharma et al, 2022) and vibrotactile (DT25, DT50, and DT100) test trains (Ng et al, 2020). The cross-modal regular comparisons that spanned 12-44, 24-88, and 48-176 Hz for stimuli DA/DT25-100, respectively, were identical to experiment 1, regardless of sensory modality used for the comparison.…”
Section: Experiments 2: Doublet Burst Patternsmentioning
confidence: 99%
See 1 more Smart Citation
“…This is surprising in light of the fact that nonhuman primates can distinguish the PF of intracortical microstimulation up to ∼200 Hz, though sensitivity to changes in PF decreases at high frequencies ( Callier et al, 2020 ). While prior studies of electrocutaneous stimulation reported discriminability of pulse trains up to 100 Hz ( Anani et al, 1977 ; Szeto et al, 1979 ; Ng et al, 2020 , 2021 ), the psychophysical tasks in these prior studies were not designed to eliminate intensity cues; so, results therefrom are difficult to compare with those reported here. Indeed, intensity discrimination of direct nerve stimulation has also been observed up to 100 Hz ( Graczyk et al, 2016 ).…”
Section: Discussionmentioning
confidence: 74%
“…Considering two successive isolated pulses, the minimal interval is about 40 ms 41 , whereas with pulse trains, the limit between the flutter range (discrete events) and the continuous vibration range was evaluated at 60 Hz ( 15 ms intervals) 15 , 42 . This value has been verified using both periodic 43 , 44 and aperiodic 45 stimuli: the authors showed that the tactile sensation of frequency is determined by the duration of the silence intervals between the pulses. Intervals longer than 15 ms are crucial whereas shorter intervals have only a limited effect on the frequency evaluation, exhibiting the limit of the discrete perception below this value.…”
Section: Discussionmentioning
confidence: 78%